2019
DOI: 10.3389/fimmu.2019.02558
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal Foam Cells and Ependymal Cells in Axolotl Spinal Cord Regeneration

Abstract: A previously unreported population of foam cells (foamy macrophages) accumulates in the invasive fibrotic meninges during gap regeneration of transected adult Axolotl spinal cord (salamander Ambystoma mexicanum) and may act beneficially. Multinucleated giant cells (MNGCs) also occurred in the fibrotic meninges. Actin-label localization and transmission electron microscopy showed characteristic foam cell and MNGC podosome and ruffled border-containing sealing ring structures involved in substratum attachment, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 115 publications
(191 reference statements)
2
8
0
Order By: Relevance
“…Enrichment of the BPs related to negative regulation of peptidase activity by the upregulated genes in Yap1_KD samples was noteworthy. Our results are in accordance with earlier investigations which showed that peptidase activity is required for an appropriate regeneration process in both invertebrates and vertebrates (Dolmatov et al, 2019;Dong et al, 2021;Enos et al, 2019;Pasten et al, 2012;Rinkevich et al, 2007).…”
Section: Decreased Osteogenic and Collagen-related Gene Expression As...supporting
confidence: 94%
“…Enrichment of the BPs related to negative regulation of peptidase activity by the upregulated genes in Yap1_KD samples was noteworthy. Our results are in accordance with earlier investigations which showed that peptidase activity is required for an appropriate regeneration process in both invertebrates and vertebrates (Dolmatov et al, 2019;Dong et al, 2021;Enos et al, 2019;Pasten et al, 2012;Rinkevich et al, 2007).…”
Section: Decreased Osteogenic and Collagen-related Gene Expression As...supporting
confidence: 94%
“…In fact, ependymal cells are the only cell types in the brain that form significant numbers of lipid droplets under nonpathological conditions, albeit at lower levels in young animals and increasing with age ( Capilla-Gonzalez et al, 2014 ; Bouab et al, 2011 ). Internalization of CSF lipoprotein particles may contribute to lipid droplet formation in ependymal cells, as they express several lipoprotein receptors including CD36 and low-density lipoprotein receptors LRP1 and LRP2 ( Matsumoto et al, 2015 ; Enos et al, 2019 ; Gajera et al, 2010 ). Consistently, in animals fed a high-fat diet, ependymal cells in the hypothalamus that regulate nutrient intake have more lipid droplets ( Zhang et al, 2013 ; Rawish et al, 2020 ).…”
Section: Cell Type Specificity Of Lipid Droplets In the Brainmentioning
confidence: 99%
“…The amount of LDs in ependymal cells, however, increases with age [ 173 , 174 ] and also in animals fed with a high-fat diet [ 175 , 176 ]. Consistent with this, the accumulation of LDs in ependymal cells has been linked to high expression levels of lipid scavenger receptors CD36 and LRP (i.e., LDL receptor-related protein) 1 and 2 [ 177 , 178 , 179 ]. The role of LDs in ependymal cells with respect to brain function still needs to be determined in the future.…”
Section: Lipid Droplets In Ependymal Cellsmentioning
confidence: 79%